Evaluation of the data contained in the requests for the anatomopathological examination of the breast in the surgery of exchange or explantation of silicone breast implants: analysis of 251 cases - Jaime Anger; Gerusa Biagione Tiburzio; Giuliana Dilay Oba; Daniela Antunez; Fernando Augusto Soares (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: The description of the Anaplastic Large Cell Lymphoma and the explantation surgery resulted in an increase of histopathological exams in breast implant removing surgery. Methods: 251 pathology requests were studied. The following data from the medical requests were analyzed: gender, age, type of surgery, number of specimens containers sent, laterality, anatomical and spatial location, clinical history, signs and symptoms, previous radiotherapy, previous chemotherapy, diagnostic hypothesis, previous surgeries, and reference to previous breast exams. Results: The mean age was 43 years old. Laterality was not mentioned in 16 requests. The surgery performed was mentioned in 15.94% requests. The number of containers varies from 1 to 5, with a median of 2. The containers include capsules in 242 cases, 161 as isolated capsule, 27 mammary tissue, and capsule in the same specimen, 54 mammary tissues sent in a separate container, anatomical and spatial location was mentioned in 6.33% cases. The detailed clinical data was included in 19.12%, signs and symptoms 13.94%, contracture as the only item mention in 64 of them. In 27 requests, lymphoma evaluation was requested. 15 included seroma and from nine of those, liquid was sent with a request for immunohistochemical and cytology analysis. None of the requests had any data on implant type or brand. Conclusion: The amount of information contained in the medical request forms is minimal. The authors recommend the need for a protocol to standardize the surgical removal of the capsule and the adjacent mammary tissue. Surgical specimens should be spatially oriented.